Experimental Investigation and Optimization on Friction Stir Welding of Nylon 6A Using Taguchi and ANOVA with Microstructural Analysis. (18th September 2021) - Seshu Kumar, G. S. V.; Kumar, Anshuman; Rajesh, S.; Chekuri, Rama Bhadri Raju; Adigo, Amsalu Gosu
Abstract : Friction stir welding is an environmentally friendly process of joining due to the nonusage of flux, or any shield gas, and it does not produce any harmful gases when compared to the joining process of fusion. Therefore, this article proposes an experimental investigation and optimization technique for studying the process of FSW on nylon 6A or polycaprolactam polymer composite plates. Specifically, the influence of input operating process parameters such as tool rotational speed (TRS), feed rate, and pitch values on the output response parameters like ultimate tensile strength (UTS) and hardness of welded joints is examined. In addition, L 27 orthogonal array of Taguchi approach is employed for the optimization of design experiments of FSW parameters. The experimental setup is carried out with various process parameter combinations like 500 rpm, 1000 rpm, and 1500 rpm as TRS, and 30 mm, 40 mm, and 50 mm as feed rate by varying the pitch values as 1 mm, 2 mm, and 3 mm. Further, the analysis of variance (ANOVA) is also employed for finding the significant parameters of input process using the regression analysis equations. Finally, microstructural analysis is used to assess the mixing or dispersing uniformity of composites effectively.